State-centric data governance in China - Alex He (Centre for International Governance Innovation (CIGI), 2023)
China's state-centric data governance regime has evolved into a framework characterized by the pursuit of a dual goal to bolster both economic growth and national security at the expense of personal information protection, which is significantly compromised due to the government's mostly unfettered access to personal data. This paper examines three components of data governance in China and then considers data governance institutions in the country. It describes how digital platform governance and regulation on cross-border data flows have illustrated the country's dual goal. The paper concludes with a discussion of the global implications of China's data governance system.
Keywords: 330